Working from Home (WFH): Challenges and Practicality for Construction Professional Personnel - Suratkon, Azeanita; Syahmina Azlan, Atiqah (International Journal of Sustainable Construction Engineering and Technology, 2021)
Implementing working from home (WFH) is seen as the most effective approach to control the number of coronavirus disease (COVID-19) infections cases in Malaysia. However, when operating from home, the crucial problem is the need for existing workers to transition from working in an office to home. By doing so, the reliance on the Internet of Things (IoT) technology significantly increases as workers are forced to conduct work online. Hence, this study aims to explore the challenges of WFH among construction professional personnel and their preferences using IoT technology in contributing to their work effectiveness. A questionnaire survey through Google Form was released, and 65 respondents living in Selangor participated in this survey. The data collected was analysed descriptively. The results revealed that respondents experienced some key challenges related to social connectivity, emotional support and sense of belonging, mental and physical health, and fear of job security during WFH. Microsoft Team and Zoom are main platforms always used for virtual meeting. The use of IoT technology for design work and site monitoring during WFH is still very limited. In conclusion, WFH is practical among construction professional personnel despite the challenges they experienced. To overcome the challenges, improvement of WFH policy is required for the future of construction industry practitioners. The finding of this study helps understand Malaysia’s key practitioners’ experience with WFH and the progress of IoT technology during the pandemic.